2001
DOI: 10.1128/jvi.75.18.8524-8537.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Immunodeficiency Virus Transcription in T Cells Revisited: NF-κB p65 Stimulates Transcriptional Elongation

Abstract: Human immunodeficiency virus type 1 (HIV-1) is able to establish a persistent latent infection during which the integrated provirus remains transcriptionally silent. Viral transcription is stimulated by NF-B, which is activated following the exposure of infected T cells to antigens or mitogens. Although it is commonly assumed that NF-B stimulates transcriptional initiation alone, we have found using RNase protection assays that, in addition to stimulating initiation, it can also stimulate elongation from the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 52 publications
(67 reference statements)
8
108
0
Order By: Relevance
“…This observed decrease in k off with TNF induction leads to extended duration of bursts and is consistent with the reported inhibition of p50-HDAC1 repressivecomplex formation at LTR NFκB sites by p50/RelA heterodimers (33)-the successful formation of HDAC1 leads to weakened recruitment of RNA polymerase II and weakened transcriptional initiation (34). The observed increases in k on are also consistent with increased recruitment of RNA polymerase II to the LTR promoter NFκB sites induced by TNF (35,36). Fitted parameter estimates of LTR residency time in the presence of TNF were used to represent an average over the first 12 h of stimulation given the dynamic nonlinear nature of the NFκB response (37,38).…”
Section: Resultssupporting
confidence: 76%
“…This observed decrease in k off with TNF induction leads to extended duration of bursts and is consistent with the reported inhibition of p50-HDAC1 repressivecomplex formation at LTR NFκB sites by p50/RelA heterodimers (33)-the successful formation of HDAC1 leads to weakened recruitment of RNA polymerase II and weakened transcriptional initiation (34). The observed increases in k on are also consistent with increased recruitment of RNA polymerase II to the LTR promoter NFκB sites induced by TNF (35,36). Fitted parameter estimates of LTR residency time in the presence of TNF were used to represent an average over the first 12 h of stimulation given the dynamic nonlinear nature of the NFκB response (37,38).…”
Section: Resultssupporting
confidence: 76%
“…Among the NF-jB subunits, RelA has been shown to strongly trans-activate the HIV-1 LTR, by stimulating the transcriptional elongation by RNA polymerase II [9,11]. Consistently, we found that the over-expression of RelA in J1G5 cells strongly induced LTR-luciferase activity within 4-6 h (Fig.…”
Section: Resultssupporting
confidence: 71%
“…In contrast, it has been shown that p65 can also stimulate elongation from the HIV-1-LTR (70), and it is possible that NADA inhibits both the transcriptional and elongation activities of the p65 NF-B subunit; this could explain the fact that NADA is a more potent inhibitor of NF-B in the context of the full HIV-1-LTR promoter.…”
Section: Discussionmentioning
confidence: 50%